Copyright Protection by Robust Digital Image Watermarking in Unsecured Communication Channels - Layth Alasafi; Tuna Göksu; Ammar Albayati (Institute of Advanced Engineering and Science, 2017)
The transition from analog technologies to digital technologies has increased the ever-growing concern for protection and authentication of digital content and data. Owners of digital content of any type are seeking and exploring new technologies for the protection of copyrighted multimedia content. Multimedia protection has become an issue in recent years, and to deal with this issue, researchers are continuously searching for and exploring new effective and efficient technologies. This thesis study has been prepared in order to increase the invisibility and durability of invisible watermarking by using the multilayer Discrete Wavelet Transform (DWT) in the frequency plane and embedding two marks into an image for the purpose of authentication and copyright when digital content travels through an unsecured channel. A novel watermarking algorithm has been proposed based on five active positions and on using two marks. In addition to the extraction process, watermarking images will be subjected to a set of attack tests. The evaluation criteria have been the bases of assessing the value of SNR, PNSR, MAE and RMSE for both the watermarking images and the watermarking images after attacks, followed by the invisibility of the watermarking being measured before and after the attacks. Our lab results show high robustness and high quality images obtaining value for both SNR and PNSR.